The reality of the Singaporean model in the fight against corruption - Charef, Abdelkader (Dirassat Journal Economic Issue, 2016)
Unlike many Asian countries, Singapore has succeeded in reducing the phenomenon of corruption that was prevalent in the country, and this was reflected in the good performance in many of the standard indicators such as the Conference of transparency, the business environment, human development and international competitiveness report, since the suces may be attributed the political Will of the Government of People’s action Party, and is reflected in the establishment of the FBCP in corrupt practices, which is independent of the police body, is investigating the facts of corruption in the public and private sectors, and this office is headed by director follows the prime minister directly, and as well as POCA age in 1960, and the imposition of this law without discrimination, without any interference from the government. the success of this experiment contributed to the development of this country in more than 53 years Under the government of Lee Kuan Yew, who was prime minister at the time The existence of effective political will.